Analysis of the correlation between post intubation laryngeal injury with the risk factors - Indriati Purwasari; Lisa Apri Yanti; Abla Ghanie; Erial Bahar (PERHATI-KL, 2020)
ABSTRACTBackground: Post intubation laryngeal injury varies in each individual. The occurrence could not be predicted, but it might be related to age, gender, smoking, comorbidities, duration of intubation, re- intubation, the type and size of endotracheal tube, the volume and duration of cuff inflation. Knowing the risk factors could prevent and decrease the occurrence of post intubation laryngeal injury. Objective: To find out the risk factors associated with the incidence of laryngeal injury after intubation. Method: This study was a cross sectional design. The samples were taken from medical records of Intensive Care Unit/ High Care Unit patients at Dr.Mohammad Hoesin Hospital Palembang, from January to December 2019. Result: There were 59 ICU/HCU patients suffered post intubation laryngeal injuries. The injuries were varied, with laryngeal edema being the most common injury (89.8%), followed by widened posterior gap (52.5%), and subglottic ulcer (32.2%). Based on the Classification of Acute Laryngeal Injury (CALI), the most common post intubation laryngeal injury was severe injury (42.4%). Multivariate analysis found that intubation more than 7 days had 4.7 times probability of experiencing severe laryngeal injury. Discussion: In our study, there was no significant correlation between post intubation laryngeal injury with gender, comorbidities, smoking, diameter of ETT, and re-intubation. There was a significant correlation between post intubation laryngeal injury, with age, duration of intubation, and kinking type of ETT. Conclusion: There was a significant relationship between severe post intubation laryngeal injury and duration of intubation. ABSTRAKLatar belakang: Cedera laring pasca intubasi endotrakeal bervariasi antara satu individu dengan individu lain. Penyebabnya belum diketahui pasti, tetapi mungkin berhubungan dengan usia, jenis kelamin, riwayat merokok, komorbid, lama intubasi, riwayat intubasi berulang, ukuran dan jenis pipa endotrakeal, volume cuff dan lama cuff dikembangkan. Diketahuinya faktor risiko dapat mencegah dan mengurangi angka kejadian cedera laring pasca intubasi. Tujuan: Mengetahui faktor risiko yang berhubungan dengan kejadian cedera laring pasca intubasi. Metode: Penelitian observasional menggunakan rancangan potong lintang (cross sectional). Dilakukan melalui data rekam medik pasien Intensive Care Unit/High Care Unit RS Dr. Mohammad Hoesin Palembang periode Januari-Desember 2019. Hasil: Didapati 59 pasien ICU/HCU yang mengalami cedera laring pasca intubasi. Cedera yang terjadi bervariasi, edema laring adalah cedera yang paling banyak terjadi (89,8%), diikuti posterior gap yang melebar (52,5%) dan ulkus subglotis (32,2%). Berdasarkan Classification of Acute Laryngeal Injury (CALI), derajat cedera laring pasca intubasi terbanyak adalah cedera derajat berat sebanyak 25 pasien (42,4%). Hasil analisis multivariat menunjukkan bahwa lama intubasi >7 hari berpeluang 4,7 kali mengalami cedera laring derajat berat. Diskusi: Pada penelitian ini tidak didapati hubungan yang bermakna antara kerusakan laring pasca intubasi dengan jenis kelamin, penyakit penyerta, merokok, diameter pipa endotrakeal dan intubasi berulang. Didapati adanya hubungan yang bermakna antara kerusakan laring pasca intubasi dengan umur, lamanya intubasi dan pipa endotrakeal tipe kinking. Kesimpulan: Terdapat hubungan yang bermakna antara cedera laring pasca intubasi derajat berat dengan lamanya intubasi.